Comparative Evaluation of Pain Scores during Periodontal Probing with or without Anesthetic Gels - Ashank Mishra; Mandapathi Priyanka; Koppolu Pradeep; Krishnajaneya Reddy Pathakota (Anesthesiology Research and Practice)
Context. The initial periodontal examination which includes full-mouth periodontal probing is one of the discomforting procedures for a patient. Aim. To evaluate the efficacy of two local anesthetic gels in the reduction of pain during periodontal probing using Florida probe in CGP patients in comparison with manual probing. Materials and Methods. Ninety systemically healthy patients with moderate to severe CGP patients were recruited. In each patient, the quadrants were randomly assigned to manual probing with UNC-15 probe, probing with Florida probe, and Florida probing with lidocaine 10% gel and with benzocaine 20% gel. In the quadrants undergoing probing with anesthetic gels, the sites were isolated and the gel was injected using syringe and a blunt-end cannula. Pain was measured using 10 mm horizontal VAS. Statistical Analysis. The analysis was carried out using SPSS version 18. The comparison of mean VAS scores was done using repeated measures ANOVA with post hoc Bonferroni test. Results. Mean VAS for manual probing was significantly more than Florida probing. Further, the mean VAS score for Florida probing was higher than the two gels. Conclusion. It is suggested that the gels might be useful in reducing pain experienced during full-mouth periodontal probing in patients with CGP.